(untitled) (Journal of Asian Development Studies, 2024)
State failure refers to a weak writ of the government where state institutions fail to provide fundamental rights to the people. It encompasses the welfare of the State, basic freedoms of the people, and strong footings of judiciary and law. The present research will explore the repercussions of state failure in Omar Shahid Hamid’s The Party Worker and Shashi Tharoor’s Riot. Both novels present the deplorable State of affairs in their respective cities, Karachi and Zaleelgarh. The study is conducted under the theoretical framework of Diamond (2015), where democracy fails, political schism is brazenly challenged, and social institutions are at the cusp of failure. Every institution is putting the life of the people at risk, be it the judiciary, human rights, liberty, freedom, and police. The political schism is not providing law and fundamental rights to the masses. The hawkish and fiendish approach of state writ causes collateral damage to the pillars of society. Corrupt practice by the top echelons of the State abounds lawlessness, causing its people to suffer.